Pengaruh Dosis Pupuk Bokashi dan Konsentrasi Pupuk Hayati Terhadap Pertumbuhan dan Hasil Tanaman Jagung Pulut (Zea Mays Var. Ceratina) - Belia Puspitasari (Berkala Ilmiah Pertanian, 2023)
Waxy corn (Zea mays var. ceratina) has a shiny white color like wax because of its high amylopactin content. The use of chemical fertilizers can cause soil health to be disturbed and result in a decrease in cultivation yields. The use of organic fertilizers such as bokashi fertilizers and biological fertilizers is expected to be a solution in overcoming problems related to soil fertility and can increase cultivation yields. The purpose of this study was to determine the dosage of bokashi fertilizer and the concentration of biological fertilizers, as well as their interaction with the growth and yield of waxy corn. The study used a randomized block design consisting of 2 factors with 4 treatment levels, repeated 3 times. The first factor was the dose of bokashi fertilizer (A), which consisted of 4 levels, namely 0 tons/ha (A0), 15 tons/ha (A1), 20 tons/ha (A2), and 25 tons/ha (A3). ). The second factor was the concentration of biological fertilizers (B) which consisted of 4 levels namely, 0ml/L (A0), 15ml/L (A1), 20ml/L (A2), and 25 ml/L (A3). Further data were analyzed using analysis of variance. If the treatment parameters are significantly different, then the DMRT test is carried out with a level of 5%. The results showed that the interaction between the application of bokashi and biological fertilizers gave significantly different results on plant height and leaf area index. The dose of bokasi fertilizer had a significant effect on the length of the fruit with the husk, the length of the fruit without the husk, the weight of the fruit with the husk, the weight of 1000 seeds, the weight of the wet stover and the weight of the dry stover. Concentration of biological fertilizers significantly affected fruit diameter with husk, fruit weight with husk, fruit length without husk, fruit diameter without husk, fruit weight without husk, wet stover weight, and dry stover weight.